Effect of nanofibers as reinforcement on resin-based dental materials: A systematic review of in vitro studies - Laís Santos Albergaria; Cassiana Koch Scotti; Rafael Francisco Lia Mondelli; Heber Arbildo Vega; Clovis Mariano Faggion, Jr; Juliana Fraga Soares Bombonatti; Marilia Mattar de Amoêdo Campos Velo (Elsevier, 2023)
This systematic review provides an update on the effect of nanofibers as reinforcement on resin-based dental materials. A bibliographic search was conducted in MEDLINEPubMed, Embase, Web of Science, Scopus, BVS (LILACS, BBO e IBECS), Cochrane, LIVIVO, and gray literature (BDTD) to identify relevant articles up to May 2021. In vitro studies that evaluated and compared the mechanical properties of nanofibers resin-based composite materials, were eligible. No publication year or language restriction was applied, and methodological quality was assessed using two methods. In a total of 6100 potentially eligible studies, 81 were selected for full-text analysis and 35 were included for qualitative analysis. Of the 35 included studies, a total of 29 studies evaluated the flexural strength (FS) of the materials. These groups were distinguished according to the resin-based materials tested and nanofiber types. Most of the studies evaluated materials composed of glass fibers and demonstrated higher values of FS when compared to resin-based materials without nanofibers. The incorporation of nanofibers into resin-based dental materials improved the mechanical properties compared to resin-based materials without nanofibers, suggesting better performance of these materials in high-stressbearing application areas. Further clinical studies are required to confirm the efficacy of resin-based materials with nanofibers.